A Mechanochemical Reaction Cascade for Controlling Load‐Strengthening of a Mechanochromic Polymer. (25th September 2020) - Pan, Yifei; Zhang, Huan; Xu, Piaoxue; Tian, Yancong; Wang, Chenxu; Xiang, Shishuai; Boulatov, Roman; Weng, Wengui
Abstract: We demonstrate an intermolecular reaction cascade to control the force which triggers crosslinking of a mechanochromic polymer of spirothiopyran (STP). Mechanochromism arises from rapid reversible force‐sensitive isomerization of STP to a merocyanine, which reacts rapidly with activated C=C bonds. The concentration of such bonds, and hence the crosslinking rate, is controlled by force‐dependent dissociation of a Diels–Alder adduct of anthracene and maleimide. Because the adduct requires ca. 1 nN higher force to dissociate at the same rate as that of STP isomerization, the cascade limits crosslinking to overstressed regions of the material, which are at the highest rate of material damage. Using comb polymers decreased the minimum concentration of mechanophores required to crosslinking by about 100‐fold compared to previous examples of load‐strengthening materials. The approach described has potential for controlling a broad range of reaction sequences triggered by mechanical load. Abstract : A mechanochemical reaction cascade for controlling load‐strengthening of a mechanochromic polymer is realized by using two comb polymers, each containing either spirothiopyran or a Diels–Alder adduct in the proximity of the branch points. The threshold force to trigger crosslinking is increased by ca. 1 nN and the minimum concentration of mechanophores required for crosslinking is decreased by 100‐fold compared to previous examples.